Perceptions of Traditional Herbal Integration in Modern Pharmacy Services Among Indigenous Communities - Ismedsyah, Ismedsyah; Maa’idah, Ulfa Nur; Astutik, Yuli (PT FORMOSA CENDEKIA GLOBAL, 2025)
This qualitative study explores indigenous communities’ perceptions of integrating traditional herbal medicines into modern pharmaceutical services. Through semi-structured interviews with 15 herbal users, traditional practitioners, and pharmacists in Medan, the findings reveal that indigenous communities view integration as a means to enhance legitimacy and access, though concerns persist regarding authenticity, safety, and commercialization. Pharmacists generally support integration but face regulatory and standardization challenges, while traditional practitioners stress the preservation of cultural values. The study concludes that successful integration requires cultural sensitivity, regulatory alignment, and collaboration between pharmacists and traditional healers to support a more inclusive health system.